2015
DOI: 10.7150/ijms.11911
|View full text |Cite
|
Sign up to set email alerts
|

Chewing Maintains Hippocampus-Dependent Cognitive Function

Abstract: Mastication (chewing) is important not only for food intake, but also for preserving and promoting the general health. Recent studies have showed that mastication helps to maintain cognitive functions in the hippocampus, a central nervous system region vital for spatial memory and learning. The purpose of this paper is to review the recent progress of the association between mastication and the hippocampus-dependent cognitive function. There are multiple neural circuits connecting the masticatory organs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(117 citation statements)
references
References 79 publications
4
105
0
4
Order By: Relevance
“…We and others have already shown that tooth extraction in rodents can also induce functional and structural changes in both glial and neuronal cells within brain regions involved in processing orofacial sensory and motor functions as well as cognitive and emotional behaviors (Avivi-Arber et al, 2014, 2015; Varathan et al, 2014; Chen et al, 2015; Watase et al, 2016). High resolution sMRI in rodents can provide an excellent readout of anatomical brain changes in mice following nerve injury, housing in an enriched environment, or maze training and such changes are also associated with cellular and molecular changes (Seminowicz et al, 2009; Lerch et al, 2011b; Cahill et al, 2015; Scholz et al, 2015a).…”
Section: Introductionmentioning
confidence: 96%
“…We and others have already shown that tooth extraction in rodents can also induce functional and structural changes in both glial and neuronal cells within brain regions involved in processing orofacial sensory and motor functions as well as cognitive and emotional behaviors (Avivi-Arber et al, 2014, 2015; Varathan et al, 2014; Chen et al, 2015; Watase et al, 2016). High resolution sMRI in rodents can provide an excellent readout of anatomical brain changes in mice following nerve injury, housing in an enriched environment, or maze training and such changes are also associated with cellular and molecular changes (Seminowicz et al, 2009; Lerch et al, 2011b; Cahill et al, 2015; Scholz et al, 2015a).…”
Section: Introductionmentioning
confidence: 96%
“…Chewing is also an effective stress-coping behavior [50][51][52]. Recent basic and clinical investigations have shown that chewing may alleviate stress-induced responses, such as increases in noradrenaline turnover in rat hypothalamus, and impaired spatial memory due to an increase in GC receptor expression in the hippocampus [51,52].…”
Section: Active Mastication Ameliorates Chronic Stressinduced Bone Lossmentioning
confidence: 99%
“…Unfortunately, neither paper showed scatter plots that would have provided clues about the behavioral relevance of the variation in BrdU-labeled neurons and the behavior scores. Nonetheless, it would be interesting to investigate whether strong chewing in elderly humans might convey the same mental benefits as other forms of more demanding physical exercise [Chen et al, 2015].…”
Section: Research Findings In Ahn and Their Perception By The Publicmentioning
confidence: 99%